Partmo business case: a decision to compete in the future - Oliva, Ismael (Estudios de Administración, 2013)
On 2011, the Colombian company called Industrias Partmo S.A. had become one of the leaders in the filter industry for light, medium and heavy vehicles. The company was recognized in the auto parts industry thanks to its concern to offer its customers quality filters, good service and affordable prices. During the last Board meetings in June 2012, led by its President, General Manager and Deputy General Manager Celestino Arango, they analyzed the Company's positioning in each of the market segments in which it operated and especially in the light vehicle segment, in which the Company was facing a possible decrease in its profitability and a loss in market share, due to the enormous pressure exerted by some distributors of filters produced in China, through lower prices. The Deputy General Manager Celestino Arango stated that it was impossible for the Company to sell filters for light vehicles at the same prices offered by companies that sold filters of Chinese origin, due to the cost structure that the Company had. Arango's concern had not been less due to the fact that approximately 38% of the company's sales had come from the light weight segment, in addition to the importance that it had meant for the company to continue to be leaders in this segment. Due to this situation, the Company had to lower its prices and the Deputy General Manager analyzed different alternatives that would allow it to face stiff competition and thus not put Partmo's position at risk.